The economic effects of a central bank reacting to house price inflation - Guido Baldi (Journal of Housing Economics, 2014)
What are the economic effects of a central bank that takes the evolution of house prices into account? In an attempt to answer this question, we use a New Keynesian dynamic stochastic general equilibrium model with a housing sector to explore the economic impacts of a central bank reacting to house price inflation. We examine this in the context of two different shocks that are associated with two factors cited as possible underlying sources of the recent bubble in the housing market and the ensuing financial crisis. First, we allow for a positive shock to the household borrowing constraint. Second, we analyze the effects of a preference shock to housing. Our results indicate that these two shocks lead to a more pronounced increase in house prices and an expansion of the housing sector if the central bank does not react to house prices. If the central bank reacts to house price increases, it must accept lower output growth rates over the business cycle. We also show that welfare decreases if a central bank reacts to house price inflation. Because of these effects, a central bank may be reluctant to react to house price inflation.
Keywords: E21; E22; E58; R21; 330; Housing Demand; House Prices; Interest Rates; Consumption and Saving